Analisis Kebijakan Bebas Visa Kunjungan Singkat (BVKS) Terhadap Sektor Pariwisata di Kota Makassar - Andi Meganingratna; Adelita Lubis; Rizky Aftaria; Alvin Septian (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
The flow of globalization has a major impact on the movement of people from one country to another. Humans move for a variety of purposes, some of which are driven by economic factors and there are for tourism as well. The authorities of a country impose conditions on foreigners when entering its territory. A visa is a document requirement that a person intending to enter the territory of another country must complete. This study aims to see the implications of the Policy of Short-Stay Visa imposed by the Indonesian government on increasing foreign tourist, especially in Makassar City. This study uses a descriptive method with a qualitative approach using the theory of national interests and national policies. With these tools, it is hoped that this research will explain the implications of the implementation of the visa-free visit policy on tourism in Makassar City. The result of this study found that BVKS has a significant effect towards Makassar Tourism however, it must be formulated with policies that encourage promotion of Makassar Tourism.